I want to die but I still want to eat tteokbokki : further conversations with my psychiatrist - Paek, Se-hŭi, 1990- (Bloomsbury, 2024)
"In this frank sequel to I Want to Die but I Want to Eat Tteokbokki, Sehee continues to document her treatment for depression and anxiety. Organized into 14 essays, each themed after one of Sehee's insecurities and framed by recorded conversations between the author and her psychiatrist, this memoir digs deeper than its predecessor."--